2012
DOI: 10.1152/ajpheart.01106.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic stimulation increases dispersion of repolarization in humans with myocardial infarction

Abstract: The sympathetic nervous system is thought to play a key role in genesis and maintenance of ventricular arrhythmias. The myocardial effect of sympathetic stimulation on myocardial repolarization in humans is poorly understood. The purpose of this study was to evaluate the effects of direct and reflex sympathetic stimulation on ventricular repolarization in patients with postinfarct cardiomyopathy (ICM). The effects of direct sympathetic stimulation were assessed using isoproterenol, while those of reflex sympat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 30 publications
7
116
0
Order By: Relevance
“…Changes in functional responses at remote regions may be mediated by changes to the ICN. The observations in the present study are consistent with findings in humans where the remote myocardium in humans showed attenuated ARI shortening in response to reflex sympathetic stimulation induced by nitroprusside (24).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Changes in functional responses at remote regions may be mediated by changes to the ICN. The observations in the present study are consistent with findings in humans where the remote myocardium in humans showed attenuated ARI shortening in response to reflex sympathetic stimulation induced by nitroprusside (24).…”
Section: Discussionsupporting
confidence: 92%
“…To describe functional innervation patterns, the percent ARI shortening from baseline was computed from five to eight electrodes in each prespecified region during RSG, LSG, and BSG stimulation, as previously described (3,24).…”
Section: Infarct Induction Animal Experimentation Was Approved By Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in infarcted hearts, bipolar voltage electroanatomic mapping was performed as described above, and location of each electrode overlying scar, border zone, or viable myocardium meticulously was noted. ARI was analyzed from unipolar electrograms of each electrode using iScaldyn (University of Utah, Salt Lake City, Utah, USA) (47,54,55). Briefly, activation time was defined from the origin to the minimum dV/dt of the activation wavefront of the unipolar electrogram, and recovery time was defined as the start of activation to the maximum dV/dt of repolarization wavefront.…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigators have reported the role of repolarisation dispersion on the basis of ventricular malignant arrhythmias in heart failure patients [8][9][10]. Heterogenity of ventricular repolarisation facilitates transmural early after depolarization propagation and also can cause intramural conduction blocks that predispose to re-entrant tachyarrhythmias [11].…”
Section: Discussionmentioning
confidence: 99%